Respon Pertumbuhan dan Hasil Tanaman Pare (Momordicha charantia L) Varietas Lipa F1 pada Berbagai Taraf Ketebalan Mulsa Jerami Padi - Wangga Gunadi; Kuswarini Sulandjari; Muhammad Syafi'i (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2021)
Bitter melone (Momordica charantia L) is a type of vegetable that is easy to cultivate and their growth does not depend on season conditions, so that bitter melon plants can grow wild in abandoned land, or are usually planted in yards by propagating into fences, bitter melon (Momordica charantia L) is one a vegetable commodity that has commercial potential when cultivated on an agribusiness scale. The purpose of this research was to measure the thickness of straw mulch which gave the best response to the growth and yield of bitter melon. This research was from August to September 2020, the method used in this experiment used a single factor randomized block design (RBD) method consisting of 5 treatments, namely: A (No Mulch), B (MPHP), C (2 cm Thickness Straw Mulch), D (4 Thickness Straw Mulch) cm), E (Straw Mulch with 6 cm thickness) with 5 replications, then if there is a treatment that has a significant effect, further analysis is carried out using LSD 5%. The significant effect of using several thickness levels of rice straw mulch on all growth characters (35 das) and yield (57 das) of bitter melon plants was observed. Straw mulch thickness of 6 cm gave the best results on the characters of plant length (129.33 cm), stem diameter (5.112 mm), number of fruits (0.92), fruit length (19.17 cm), fruit diameter (35.272 mm), weight the fruit of the plant (176.4 g), and the weight of the fruit per bed ( 1,461 kg equal to 1.76 ton/ ha). However, of this research the Black and Silver Plastic Mulch (MPHP) as control treatment had better results on all growth and production characteristics of bitter melon plants. Keywords: crop yields, straw mulch,bitter melon, plant growth, thickness level